Escrita autobiográfica e autoria em memoriais de professores de Língua Portuguesa - Cunha, Djenane Sichieri Wagner (2013)
The general objective of this research is to contribute to the expansion of knowledge concerning teachers´ autobiographical productions and how the process of authorship development involved in them happens. The research is justified because we realize how much the school, with its authoritative discourse, imposes upon the subject the meaning which is institutionally legitimized, and we see the production of memorials as an opportunity for change in this process, by allowing him to write about himself, takes responsibility for his writing and be heard. We analyzed, based on the theoretical principles of discourse analysis, ten memorials produced by Portuguese language teachers who were attending Pedagogy as a second undergraduate course. We made an incursion in researches that conceptualize postmodernism and deal with identity and subjectivity and later, in the memorials analysis, a profile outline of the participants. We also observed in our analysis the point of view of the course participants regarding the production of the memorials. We based our studies on authors who address the notion of authorship to also analyze how it is expressed in the course participants textual productions. In the methodology adopted, we listed some categories that were observed in extracts taken from memorials, so that we could understand how the subject reveals maturity in his writing. In the analysis we retrieved the concepts of drift and dispersion observed in some sections of the memorials how they become evident. As evidence of authorship to be observed in the memorials, we selected the categories: writing and grammatical resources, the subject's relationship with his own writing process, reproduction of other voices, concern with the reader, originality and adjectives and adverbs. The results observed denote that the course participants have demonstrated the understanding of writing, take responsibility for their writing, and, therefore, take on the position of author. Autobiographical writing appears, therefore, as a resource to be used in teacher education providing moments for reflection concerning teachers identity construction of and their teaching practice